Comparison of 3 Grading Systems (House-Brackmann, Sunnybrook, Sydney) for the Assessment of Facial Nerve Paralysis and Prediction of Neural Recovery - Norhafiza MAT LAZIM; Hamizah ISMAIL; Sanihah ABDUL HALIM; Nik Adillah NIK OTHMAN; Ali HARON (Medeniyet Medical Journal)
Objective: Currently, multiple classification systems exist for the assessment of facial nerve paralysis. This study was designed to choose the most practical system for use in a clinical setting depending on the clinician need. We compared the responsiveness of the 3 facial nerve grading systems, i.e., House-Brackmann, Sydney, and Sunnybrook, as the subjective method and compared the outcomes with the objective method, i.e., the nerve conduction study. The correlation between the subjective and objective assessments was determined. Methods: A total of 22 consented participants with facial palsy was assessed with photos and videography recordings where they performed 10 standard facial expressions. The severity of facial paralysis was evaluated with the House-Brackmann, Sydney, and Sunnybrook grading scales subjectively and with the facial nerve conduction study objectively. The assessments were repeated after 3 months. Results: A Wilcoxon signed-rank test showed that there were statistically significant change in all three gradings after 3-month of assessment. The responsiveness of the nerve conduction study was significant for the nasalis and orbicularis oris muscles. It was not significant for the orbicularis oculi muscle. The nasalis and orbicularis oculi showed statistically significant correlation with the three classification systems except for the orbicularis oculi muscle. Conclusions: All three grading systems, House-Brackmann, Sydney, and Sunnybrook, showed statistically significant responsiveness after 3 months of evaluation. The nasalis and orbicularis oculi muscle can be used to predict facial palsy recovery because they showed strong positive and negative correlations with the extent of facial nerve degeneration from the nerve conduction study.